Hypothesis: is accumulation of a furan dicarboxylic acid (3-carboxy-4- methyl-5-propyl-2-furanpropanoic acid) related to the neurological abnormalities in patients with renal failure? - Costigan, MG; Callaghan, C; Lindup, W (1996)
The Plasma concentrations of a lipophilic furan dicarboxylic acid (3- carboxy-4-methyl-5-propyl-2-fluranpropanoic acid; 5-propyl FPA), which is highly bound to albumin and not removed by haemodialysis, have been measured in patients with renal impairment who were not dialysis dependent or who were treated by either haemodialysis or peritoneal dialysis. Neurological abnormalities were assessed as absent, moderate, or severe. A relationship was observed between the increasing severity of abnormalities attributable to the uraemic state and the higher plasma concentrations of 5-propyl FPA. There are theoretical grounds for believing that 5-propyl FPA contributes to these neurological abnormalities because of its structure and also because it inhibits the transport of organic acids in the kidney and could do likewise at the blood-brain barrier.